Acceptability and Effectiveness of Assisted Human Immunodeficiency Virus Partner Services in Mozambique: Results From a Pilot Program in a Public, Urban Clinic. Issue 11 (November 2016) - Myers, R. Serene; Feldacker, Caryl; Cesár, Freide; Paredes, Zulmira; Augusto, Gerito; Muluana, Chadreque; Citao, Sinesia; Mboa-Ferrao, Catarina; Karajeanes, Esmeralda; Golden, Matthew R.
Abstract : Background: Assisted partner services (APS) involves offering persons with human immunodeficiency virus (HIV) assistance notifying and testing their sex partners. Assisted partner services is rarely available in sub-Saharan Africa. We instituted a pilot APS program in Maputo, Mozambique. Methods: Between June and September 2014, community health workers (CHWs) offered APS to persons with newly diagnosed HIV (index patients [IPs]). Community health workers interviewed IPs at baseline, 4 and 8 weeks. At baseline, CHWs counseled IPs to notify partners and encourage their HIV testing, but did not notify partners directly. At 4 weeks, CHWs notified partners directly. We compared 4- and 8-week outcomes to estimate the impact of APS on partner notification, HIV testing and HIV case finding. Results: Community health workers offered 223 IPs APS, of whom 220 (99%) accepted; CHWs collected complete follow-up data on 206 persons; 79% were women, 74% were married, and 50% named >1 sex partner. Index patients named 262 HIV-negative partners at baseline. At 4 weeks, before APS, IPs had notified 193 partners (74%), but only 82 (31%) had HIV tested; 43 (13%) tested HIV positive. Assisted partner services resulted in the notification of 22 additional partners, testing of 83 partners and 43 new HIV diagnoses. In relative terms, APS increased partner notification, testing, and HIV case finding by 13%, 101%, and 125%. Seventy-two (35%) of 206 IPs were in ongoing HIV serodiscordant partnerships. Only 2.5 IPs needed to receive APS to identify a previously undiagnosed HIV-infected partner or an ongoing HIV serodiscordant partnership. Two (1%) IPs reported APS-related adverse events. Conclusions: Assisted partner services is acceptable to Mozambicans newly diagnosed with HIV, identifies large numbers of serodiscordant partnerships and persons with undiagnosed HIV, and poses a low risk of adverse events. Abstract : An evaluation of a human immunodeficiency virus partner notification program in Mozambique found that the intervention is acceptable, safe, and effective in identifying partners with undiagnosed human immunodeficiency virus and persons in serodiscordant partnerships.